ANALISIS KESALAHAN BERBAHASA PADA TEKS PIDATO SISWA KELAS VIII H SMP NEGERI 1 SUNGAI RAYA - Amalia, Chika; Seli, Sesilia; Heryana, Nanang (Universitas Tanjungpura, 2025)
This study aims to identify and analyze the language errors in speech texts written by eighth-grade students at SMP Negeri 1 Sungai Raya. The errors analyzed include spelling, diction, and sentence structure. The method used in this study is qualitative descriptive. The data collection technique involves analyzing speech text documents written by eighth-grade students of class VIII H. The data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of this study show that errors are found in the aspects of spelling, diction, and sentence structure. In the spelling aspect, 146 errors were identified, including errors in capitalization, lowercase letters, italics, root words, affixed words, reduplication, prepositions, abbreviations, and punctuation. In the diction aspect, 31 errors were found, including inaccuracies in word choice, conjunction errors, and abbreviation writing errors. Lastly, in the sentence structure aspect, 27 errors were identified, including sentence conciseness, sentence ambiguity, sentence incoherence, and subject repetition.